2022
DOI: 10.3390/vaccines10101721
|View full text |Cite
|
Sign up to set email alerts
|

Seven Fatty Acid Metabolism-Related Genes as Potential Biomarkers for Predicting the Prognosis and Immunotherapy Responses in Patients with Esophageal Cancer

Abstract: Background: Esophageal cancer (ESCA) is a major cause of cancer-related mortality worldwide. Altered fatty acid metabolism is a hallmark of cancer. However, studies on the roles of fatty acid metabolism-related genes (FRGs) in ESCA remain limited. Method: We identified differentially expressed FRGs (DE-FRGs). Then, the DE-FRGs prognostic model was constructed and validated using a comprehensive analysis. Moreover, the correlation between the risk model and clinical characteristics was investigated. A nomogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…This cluster has three cluster-specific genes, GOLT1A, RAB27B and SLC28A3. GOLT1A has been reported to be differentially expressed between high and low risk groups for esophageal cancer [ 50 ] and RAB27B is a significant prognostic marker for metastasis and poor prognosis in colorectal cancer [ 51 – 53 ]. The TF that appears in the models of all three hit genes is GATA-binding factor 2 (GATA2).…”
Section: Resultsmentioning
confidence: 99%
“…This cluster has three cluster-specific genes, GOLT1A, RAB27B and SLC28A3. GOLT1A has been reported to be differentially expressed between high and low risk groups for esophageal cancer [ 50 ] and RAB27B is a significant prognostic marker for metastasis and poor prognosis in colorectal cancer [ 51 – 53 ]. The TF that appears in the models of all three hit genes is GATA-binding factor 2 (GATA2).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, lncRNAs such as LINC01068, TMEM92-AS1 and AC243967.2 have been reported to be correlated with iron metabolism and iron death, and be closely related to the infiltration of immune cells in ESCC[ 133 ]. Moreover, Zhang et al [ 134 ] reported that mitochondrial energy metabolism is associated with the TIME and poor prognosis in ESCC patients, and identified several fatty acid metabolism-related genes that are predictors of EC prognosis[ 135 ]. Additionally, tryptophan-derived metabolites have been shown to contribute to tumor immune escape, and been identified as biomarkers for EC metastasis and prognosis[ 136 ].…”
Section: Tumor Cell-related Immunosuppressive Factorsmentioning
confidence: 99%